Comparative Analysis Of Digital Marketing On Customer Loyalty At SUMSELPOST And MATTANEWS - Putri, Alfirdausya Eyara; Ermelia, Sri; Harahap, Lily Rahmawati (Jurnal Fokus Manajemen, 2025)
This study aim to determine the comparison of digital marketing on customer loyalty between SumselPost and Mattanews in the city of Palembang. This tudy uses a quantitative and qualitative approach. Quantitative data was obtained through the distribution of questionnaires to respondents and processed using SPSS software to be analyzed statistically. Qualitative data was obtained from interviews and observations as a complement to provide an in-depth explanation of the quantitative results. Statistic analysis used a comparative hypothesis test in the form of an Independent Sample T-test to see whether there were differences between the two companies. The results of the study show that there is no significant differences in the implementation of digital marketing and customer loyalty between SumselPost and Mattanews. There are slight differences in strategy between the two companies but statistically not sufficient to provide a significant difference.